2006
DOI: 10.1111/j.1600-0420.2006.00633.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cyclic 
guanosine‐monophosphate on porcine retinal vasomotion

Abstract: ABSTRACT.Purpose: Vasomotion refers to periodic oscillations in vascular tone that ensure the intermittent supply of blood to adjacent microvascular units. Previous evidence from vessels outside the eye suggests that cyclic guanosine-monophosphate (cGMP) is involved in the regulation of vasomotion, but it is unknown whether this compound has an effect on vasomotion in retinal vessels. Methods: Retinal arterioles from porcine eyes were studied in a wire myograph. After initiation of vasomotion, the vessels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 31 publications
(37 reference statements)
0
21
0
Order By: Relevance
“…The same is the case for procedures aimed at manipulating the concentration of cGMP within the vascular wall. Inhibition of endothelial NO synthase or guanylate cyclase (the latter of which produces cGMP in response to NO) may either inhibit vasomotion Hessellund et al 2006) or leave it more or less unaffected (Mauban & Wier 2004). Whereas in the present mesenteric vessel preparation we consistently find that the addition of 8Br-cGMP promotes synchronization Peng et al 2001;Rahman et al 2005), Haddock et al (2006) did not find this effect on adding dibutyryl-cGMP to endothelium-denuded rat cerebral arteries.…”
Section: Discussionmentioning
confidence: 43%
“…The same is the case for procedures aimed at manipulating the concentration of cGMP within the vascular wall. Inhibition of endothelial NO synthase or guanylate cyclase (the latter of which produces cGMP in response to NO) may either inhibit vasomotion Hessellund et al 2006) or leave it more or less unaffected (Mauban & Wier 2004). Whereas in the present mesenteric vessel preparation we consistently find that the addition of 8Br-cGMP promotes synchronization Peng et al 2001;Rahman et al 2005), Haddock et al (2006) did not find this effect on adding dibutyryl-cGMP to endothelium-denuded rat cerebral arteries.…”
Section: Discussionmentioning
confidence: 43%
“…Vasomotion refers to periodic oscillations in vascular tone that ensure the intermittent supply of blood to adjacent microvascular units [19,20] . Blood flow (Q) through the vessel is determined by the pressure difference between the two ends L-NAME 10 mg/ml L-NAME 20 mg/ml L-NAME 30 mg/ml L-Arg 100 mg/ml of the vessel (P1 -P2) and the vascular resistance (R) according to Ohm's law: P1 -P2 = Q !…”
Section: Discussionmentioning
confidence: 99%
“…Vasomotion refers to periodic oscillations in vascular tone that allow fine control of the capillary blood and facilitate exchange of metabolites, being a phenomenon described in practically all vascular beds. It has been assumed that in vitro techniques can serve as models for studying the mechanisms underlying vasomotion in vivo , and previous studies have already characterized vasomotion in isolated porcine retinal arterioles [19,20] .…”
Section: Introductionmentioning
confidence: 99%
“…Vasomotion refers to periodic oscillations in vascular tone that ensure the intermittent supply of blood to adjacent microvascular units. Several studies in anesthetized cats [16,17], isolated bovine [18,19] or porcine [20,21,22,23,24] retinal arteries studied in a myograph suggest that there are basal oscillations in vascular tone. Another study revealed myogenic tone and reactivity of the isolated rat external ophthalmic artery [25].…”
Section: Discussionmentioning
confidence: 99%